Comparison of four-year toxicities and local control of ultra-hypofractionated vs moderate-hypofractionated image guided prostate radiation with HDR brachytherapy boost: A phase I-II single institution trial. (May 2023) - Beaudry, M.M.; Carignan, D.; Foster, W.; Lavallee, M.C.; Aubin, S.; Lacroix, F.; Poulin, E.; Lachance, B.; Després, P.; Beaulieu, L.; Vigneault, E.; Martin, A.G.
Highlights: There is a rationale to support the use of hypofractionation and dose escalation in localized prostate cancer. The toxicity profile and local control with ultra-hypofractionated radiation therapy (UHF) and a brachytherapy boost (BB) compares favorably with the other standard moderate hypofractionated regimens. UHF significantly reduces treatment time and is more convenient for patients. Abstract: Purpose/Objective(s): To analyze the long term efficacy and safety of an ultra-hypofractionated (UHF) radiation therapy prostate treatment regimen with HDR brachytherapy boost (BB) and compare it to moderate-hypofractionated regimens (MHF). Materials/Methods: In this single arm, prospective monocentric study, 28 patients with intermediate risk prostate cancer were recruited in an experimental treatment arm of 25 Gy in 5 fractions plus a 15 Gy HDR BB. They were then compared to two historical control groups, treated with either 36 Gy in 12 fractions or 37.5 Gy in 15 fractions with a similar HDR BB. The control groups included 151 and 311 patients respectively. Patient outcomes were reported using the International Prostate Symptom Score (IPSS) and Expanded Prostate Index Composite (EPIC-26) questionnaires at baseline and at each follow-up visit. Results: Median follow-up for the experimental arm was 48.5 months compared to 47 months and 60 months compared to the 36/12 and 37, 5/15 groups respectively. The IPSS and EPIC scores did not demonstrate any significant differences in the gastrointestinal or genitourinary domains between the three groups over time. No biochemical recurrence occurred in the UHF arm as defined by the Phoenix criterion. Conclusion: The UHF treatment scheme with HDR BB seems equivalent to standard treatment arms in terms of toxicities and local control. Randomized control trials with larger cohorts are ongoing and needed to further confirm our findings.